Analysis of Geographically and Temporally Weighted Regression (GTWR) GRDP of the Construction Sector in Java Island - Sugi Haryanto; Muhammad Nur Aidi; Anik Djuraidah (Universitas Muhammadiyah Surakarta, 2019)
The construction sector is one of the sectors that have strategic value in the national economy. Economic activity in an area is measured using the Gross Regional Domestic Product (GRDP). The development of economic activities in the construction sector can be seen from the GRDP of the construction sector. The Geographically and Temporally Weighted Regression (GTWR) model is a development of the Geographically Weighted Regression (GWR) model taking into account the diversity of locations and times. This study used secondary data, namely the data of GRDP the construction sector as a response variable and four explanatory variables, namely the number of population, local revenue, area, and the number of construction establishments. The purpose of this study is to determine the factors that influence each regency/municipality and each year observing the GRDP of the construction sector in Java with the GTWR model. GTWR model is more effective to describe the value of GRDP the construction sector of regencies/municipalities in Java Island in 2010-2016. This is indicated by the decrease in values of Root Mean Square Error (RMSE), Mean Absolute Deviation (MAD), and the Mean Absolute Percentage Error (MAPE).